Pengaruh Perendaman Larutan KOH dan NaOH Terhadap Kualitas Alginat Rumput Laut Sargassum polycycstum C.A. Agardh - Mirza, Mohamad; Ridlo, Ali; Pramesti, Rini (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Sargassum polycystum seaweed is a type of brown algae that contains alginate. Alginate from S. polycystum did not optimally and alginate has an importnat role from a variety of industries. Alginate ekstraction obtained by submersion wes using NaOH and KOH solvent, then continued using Na2CO3 solvent. The purpose of this research was to determine the effect of immersion with KOH and NaOH with concentration 0,3%, 0,5% and 0,7% solution to the quality alginate from brown seaweed S. polycystum. Experimental design used was Rancangan Acak Lengkap (RAL). The results showed that aging of the KOH solution has a lower water content and higher viscosity than NaOH solution. The concentration of the solution used also affects the yield, moisture content, ash content and viscosity alginate S. polycystum. The higher concentration of the solution then the yield, moisture content and lower ash content, while viscosity alginate increased. The best results obtained in the treatment with a solution of KOH concentration of 0.7%.